A Learnable Prior Improves Inverse Tumor Growth Modeling - Weidner, Jonas; Ezhov, Ivan; Balcerak, Michal; Metz, Marie-Christin; Litvinov, Sergey; Kaltenbach, Sebastian; Feiner, Leonhard; Lux, Laurin; Kofler, Florian; Lipkova, Jana; Latz, Jonas; Rueckert, Daniel; et al. (IEEE transactions on medical imaging, 2025)
Biophysical modeling, particularly involving partial differential equations (PDEs), offers significant potential for tailoring disease treatment protocols to individual patients. However, the inverse problem-solving aspect of these models presents a substantial challenge, either due to the high computational requirements of model-based approaches or the limited robustness of deep learning (DL) methods. We propose a novel framework that leverages the unique strengths of both approaches in a synergistic manner. Our method incorporates a DL ensemble for initial parameter estimation, facilitating efficient downstream evolutionary sampling initialized with this DL-based prior. We showcase the effectiveness of integrating a rapid deep-learning algorithm with a high-precision evolution strategy in estimating brain tumor cell concentrations from magnetic resonance images. The DL-Prior plays a pivotal role, significantly constraining the effective sampling-parameter space. This reduction results in a fivefold convergence acceleration and a Dice-score of 95%.